Coping Self-Efficacy and Stress Mindset as Predictors of Student Success Outcomes - Meg Kapil; Ramin Rostampour; Allyson Hadwin (Journal of Postsecondary Student Success, 2024)
University students experience stress from academic demands. Stress is in fact expected in academic settings and important for achieving goals. How students experience the inevitable stress in the academic context, and whether stress is a support or hindrance for them, is related to their beliefs about stress. This study examined two types of beliefs regarding academic stress: (a) perceptions of being capable of coping with academic stress and demands, named coping self-efficacy, and (b) general beliefs regarding stress itself, named stress mindset, and the impact of those two stress beliefs on two types of outcomes related to student success: academic performance (GPA) and student experiences (mental health, perceived motivation challenges). Findings indicate coping self-efficacy positively predicts higher mental health and lower motivation challenges; neither stress mindset nor coping self-efficacy predicted GPA. Coping self-efficacy in the university context, which denotes feeling capable of managing stress and academic demands, emerged as a useful predictor of student success outcomes. As eliminating stress altogether is not practical or possible, this research focuses on beliefs about stress as important for student success.